Réponses

Meilleure réponse !
2013-12-02T22:19:28+01:00
1) aire du carré est égal au carré d'un coté
donc
A(ABCD) = AD²
A(ABCD)=(a+b)²
(Je ne suis pas sure que ce soit ce qui est attendu, mais pourquoi pas)

2) fig 1 : Aire(ABCD) = (2+8)² = 10² = 100
et Aire(ABCD) = 2² + 2x8 + 2x8 + 8²
Donc (2+8)² = 2² + 2x2x8 + 8²

fig 2 : Aire(ABDC) = (7+3)² = 10² = 100
et Aire(ABCD) = 7² + 3x7 + 7x3 + 3²
Donc Aire(ABCD) = 7² + 2x3x7 + 3²

3)
(1+9)² = 1² + 2x1x9 + 9²
(4+6²) = 4² + 2x4x6 + 6²

4)
(a+b)² = a² + 2xaxb + b²

Démonstration :
(a+b)² = (a+b)(a+b)
(a+b)² = axa + axb + bxa + bxb
(a+b)² = a² + axb + axb + b²
Donc (a+b)² = a² + 2xaxb + b²